Pemulihan Stok dan Restorasi Habitat Teripang: Status Ekosistem Lamun di Lokasi Restocking Pulau Pramuka dan Pulau Kelapa Dua, Kepulauan Seribu, Jakarta - Am Azbas Taurusman; . Isdahartati; . Isheliadesti; . Ristiani (Institut Pertanian Bogor, 2013)
Global fish stock has been significantly declined over the past 3 decades, especially in coastal waters. Over-exploitation of fish resources and habitat destruction has been considered playing important role in declining the fish stock. This study was conducted to restore sea cucumbers stock in Pulau Seribu. A base line study was needed to evaluate the status of seagrass ecosystems in restocking locations. The results showed there were 8 seagrass species identified in both study sites, covering 0-65% area, consisted of 20.45 ± 11.28% in Pulau Pramuka and 6.00 ± 6.56% in Pulau Kelapa Dua, respectively. Seagrass ecosystem in Pulau Pramuka indicated better condition than that in Pulau Kelapa Dua and statistically was significantly different (global R = 0.193; p < 0.001). However, to support the restocking efforts of sea cucumbers, the seagrass habitat in both locations need to be restored.